Bicomponent fibers with improved curvature
By using the first and second polyethylene compositions with different characteristics in the two-component fiber, the problem of difficulty in simultaneously increasing the curvature and other characteristics of the fibers in the prior art is solved, and the effect of improving high curvature and multiple characteristics is achieved. .
Patent Information
- Application Number
- CN202180033534.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-08
- Filing Date
- 2021-05-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-05-05
AI Technical Summary
The prior art is difficult to obtain fibers with improved curvature while maintaining or improving the spinning, softness, recyclability and ductility of the two-component fibers.
By using the first and second polyethylene compositions with different molecular weight distributions, density and crystallization temperatures in the two-component fibers, fibers with improved curvature are formed. The specific method includes using a polyethylene composition having a weight average molecular weight ratio of less than or greater than 3.0 in the first and second regions of the fibers, respectively, and ensuring that at least one of the crystallization temperature is at least 2 higher than the other. ℃ or 3.5℃.
The two-component fibers are achieved while maintaining or improving other properties such as spinning, softness, recyclability and ductility at high curvature, providing a wider range of application possibilities.
Smart Images

Figure CN115516144B_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure are generally directed to bicomponent fibers comprising polyethylene having improved curvature, and nonwovens comprising these fibers. Background Art
[0002] Bicomponent fiber is a fiber made of two different polymer compositions, which are extruded from the same spinneret, wherein the same filament or fiber contains these two compositions. When the fiber leaves the spinneret, it is composed of non-mixed components that melt at the interface. The two polymer compositions can be different in their chemical and / or physical properties. Bicomponent fiber can be formed by conventional spinning techniques known in the art, and can be used to form nonwovens. Nonwoven fabrics have a variety of applications, such as disposable materials and diapers in filters, medical applications. In order to help reduce nonwoven weight or obtain other favorable nonwoven properties, such as bulkiness (loft), bicomponent fibers with curvature can be used. However, there is a problem of obtaining bicomponent fibers with improved curvature and maintaining or improving other favorable properties, such as spinnability, softness, recyclability and ductility while improving curvature. Summary of the invention
[0003] Embodiments of the present disclosure provide bicomponent fibers that can be used to form nonwovens and provide unique and surprisingly high curvatures in various aspects, while maintaining or improving other properties, such as spinnability, tactile softness, recyclability, and extensibility. Bicomponent fibers according to embodiments of the present disclosure each include a first region and a second region, the first region and the second region respectively comprising a first polyethylene composition and a second polyethylene composition, the first polyethylene composition and the second polyethylene composition contributing to fibers with improved curvature and favorable spinnability, softness, recyclability, and extensibility. Specifically, bicomponent fibers according to embodiments of the present disclosure include a first polyethylene composition and a second polyethylene composition, the first polyethylene composition and the second polyethylene composition can improve spinnability, softness, recyclability, and extensibility, and can be interfaced to improve the inherent curvature of the fiber (e.g., fiber curvature that is not a result of mechanical curling or post-extrusion processes (such as attenuation with heated air or applied tension)).
[0004] Disclosed herein is a bicomponent fiber. In one embodiment, the bicomponent fiber comprises a fiber centroid; a first region having a first centroid and a second region having a second centroid; the first region comprises a first polyethylene composition having a molecular weight expressed as a ratio of weight average molecular weight to number average molecular weight (M) of less than 3.0. w(GPC) / M n(GPC)) molecular weight distribution; the second region comprises a second polyethylene composition, the density of the second polyethylene composition is less than the density of the first polyethylene composition; wherein at least one of the first centroid and the second centroid is different from the fiber centroid; and wherein the crystallization temperature (Tc) of the first polyethylene composition is at least 2°C greater than the crystallization temperature (Tc) of the second polyethylene composition.
[0005] In various embodiments, the bicomponent fiber comprises a fiber centroid; a first region having a first centroid and a second region having a second centroid; the first region comprising a first polyethylene composition having a molecular weight expressed as a ratio of weight average molecular weight to number average molecular weight (M) greater than 3.0. w(GPC) / M n(GPC) ) molecular weight distribution; the second region comprises a second polyethylene composition, the density of the second polyethylene composition is less than the density of the first polyethylene composition; wherein at least one of the first centroid and the second centroid is different from the fiber centroid; wherein the crystallization temperature (Tc) of the first polyethylene composition is at least 3.5°C greater than the crystallization temperature (Tc) of the second polyethylene composition.
[0006] Also disclosed herein are nonwovens formed from the bicomponent fibers disclosed herein. For example, a spunbond nonwoven can be formed from the bicomponent fibers disclosed herein. In one embodiment, the spunbond nonwoven comprises a bicomponent fiber comprising a fiber centroid; a first region having a first centroid and a second region having a second centroid; the first region comprising a first polyethylene composition having a ratio (M) of less than 3.0 expressed as a weight average molecular weight to a number average molecular weight. w(GPC) / M n(GPC) ) molecular weight distribution; the second region comprises a second polyethylene composition having a density less than the density of the first polyethylene composition; wherein at least one of the first centroid and the second centroid is different from the fiber centroid; and wherein the crystallization temperature (Tc) of the first polyethylene composition is at least 2°C greater than the crystallization temperature (Tc) of the second polyethylene composition. In various embodiments, the spunbond nonwoven comprises a bicomponent fiber comprising a fiber centroid; a first region having a first centroid and a second region having a second centroid; the first region comprises a first polyethylene composition having a ratio (M) of weight average molecular weight to number average molecular weight greater than 3.0. w(GPC) / M n(GPC)) molecular weight distribution; the second region comprises a second polyethylene composition, the density of the second polyethylene composition is less than the density of the first polyethylene composition; wherein at least one of the first centroid and the second centroid is different from the fiber centroid; wherein the crystallization temperature (Tc) of the first polyethylene composition is at least 3.5°C greater than the crystallization temperature (Tc) of the second polyethylene composition.
[0007] Additional features and advantages of the embodiments will be set forth in the detailed description that follows, and will in part be readily apparent to those skilled in the art from that description or recognized by practicing the embodiments described herein, including the following detailed description, claims, and drawings.
[0008] It should be understood that the above and following descriptions describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate the various embodiments described herein and, together with the description, are used to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 is a scanning electron micrograph (SEM) cross-sectional image of a bicomponent fiber with an eccentric core-sheath configuration and a shifted center of mass.
[0010] Figure 2 is a graphical representation of a single reactor stream feed data flow for producing the polyethylene compositions disclosed herein.
[0011] Figure 3 is a graphical representation of dual reactor stream feed data flow for producing the polyethylene compositions disclosed herein. DETAILED DESCRIPTION
[0012] Various aspects of the disclosed bicomponent fibers are described in more detail below. Bicomponent fibers with increased curvature can be used to form nonwovens, and such nonwovens can have various applications, including, for example, wipes, masks, tissues, bandages, and other medical and sanitary products. However, it should be noted that this is merely an illustrative implementation of the embodiments disclosed herein. These embodiments are applicable to other technologies susceptible to similar problems described above.
[0013] As used herein, the terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.
[0014] As used herein, the term "interpolymer" refers to polymers prepared by polymerizing at least two different types of monomers. The term interpolymer thus includes copolymers (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0015] As used herein, the term "polymer" means a polymeric compound prepared by polymerizing monomers of the same or different types. Thus, the generic term polymer encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure) and the term interpolymer. Trace amounts of impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. The polymer may be a single polymer or a polymer blend.
[0016] As used herein, the term "polyethylene composition" refers to a polymer comprising greater than 50% by weight of units derived from ethylene monomers and optionally one or more comonomers. Polyethylene compositions include polyethylene homopolymers, copolymers, or interpolymers. Common forms of polyethylene compositions known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); ultra low density polyethylene (ULDPE); very low density polyethylene (VLDPE); single-site catalyzed linear low density polyethylene, including linear and substantially linear low density resins (m-LLDPE); medium density polyethylene (MDPE); and high density polyethylene (HDPE).
[0017] As used herein, the terms "nonwoven," "nonwoven web," and "nonwoven fabric" are used interchangeably herein. "Nonwoven" refers to a web or fabric having a structure of individual fibers or threads that are randomly interlaced rather than in an identifiable pattern as in a knitted fabric.
[0018] As used herein, the term "meltblown" refers to the manufacture of a nonwoven fabric by a process comprising the steps of: (a) extruding molten thermoplastic strands from a spinneret; (b) using a heated high-speed air stream to simultaneously quench and attenuate a polymer stream immediately below the spinneret; (c) collecting the stretched strands into a web on a collecting surface. Meltblown nonwoven webs can be bonded by a variety of means, including but not limited to autogenous bonding (i.e., self-bonding without further treatment), thermal calendering processes, adhesive bonding processes, hot air bonding processes, needle punching processes, hydroentanglement processes, and combinations thereof.
[0019] As used herein, the term "spunbond" refers to the manufacture of a nonwoven fabric comprising the following steps: (a) extruding molten thermoplastic strands from a plurality of fine capillaries known as spinnerets; (b) quenching strands of thermoplastic strands, such as polyethylene compositions, with a generally cooled air stream to promote solidification of the molten strands of the thermoplastic; (c) advancing the filaments through a quenching zone with a drawing tension to attenuate the filaments, which drawing tension may be applied by entraining the filaments pneumatically in an air stream or by winding the filaments around mechanical drawing rollers of a type commonly used in the textile fiber industry; (d) collecting the drawn strands in a mesh (e.g., a moving screen or porous strip) on a porous surface; and (e) bonding the mesh of loose strands into the nonwoven fabric. Bonding may be achieved in a variety of ways, including, but not limited to, thermal calendaring processes, adhesive bonding processes, hot air bonding processes, needle punching processes, hydroentanglement processes, and combinations thereof.
[0020] As used herein, the term "curvature" refers to the bend or curl of an individual fiber that is a result of its composition and not the result of any post-extrusion processing (e.g., mechanical crimping or attenuation by heat) that may affect the curvature or curl of the fiber. The amount of curvature of the bicomponent fibers disclosed herein can be measured according to the test method described below.
[0021] fiber
[0022] The fiber taught herein can be formed by any conventional spinning technology.For example, the first region and the second region of the bicomponent fiber can form fiber via melt spinning.In melt spinning, the first region comprising the first polyethylene composition and the second region comprising the second polyethylene composition can be melted, coextruded and forced to pass through the fine holes in the metal plate referred to as a spinneret to arrive in air or other gases, in which they are cooled and solidified, thereby forming a bicomponent fiber.The solidified fiber can be extracted via an air ejector, a rotating roller or a godet roller (godet), and can be laid on a conveyor belt as a web for forming a nonwoven.The melt-blown nonwoven comprising the bicomponent fiber according to an embodiment of the present disclosure can be formed.In other embodiments, the spunbond nonwoven comprising the bicomponent fiber according to an embodiment of the present disclosure can be formed.
[0023] Fiber disclosed herein has improved curvature and other advantageous properties, such as recyclability, tactile softness and ductility caused by being made of polyethylene. The improved curvature of fiber disclosed herein is not the result of mechanical curling or post-extrusion process (such as thinning with heated air or applying tension). The fiber in each aspect comprises all or most of polyethylene composition. The nonwoven comprising polyethylene composition is known because of its tactile softness, and the material comprising polyethylene composition is a candidate for compatibility with polyethylene recycled material stream.
[0024] In an embodiment, the curvature of the bicomponent fiber is at least 0.50 mm -1 The curvature of the bicomponent fiber can be measured according to the test method described below. The present invention discloses and includes at least 0.50 mm -1 For example, in some embodiments, the curvature of the bicomponent fiber can be at least 0.50 mm when measured according to the test method described below. -1 , 0.60mm -1 、0.70mm -1 or 0.80mm -1 In other embodiments, the curvature of the bicomponent fiber may be between 0.50 mm and 1.50 mm when measured according to the test method described below. -1 Up to 3.00mm -1 , 0.50mm -1 Up to 2.50mm -1 , 0.50mm -1 Up to 2.00mm -1 , 0.50mm -1 Up to 1.50mm -1 , 0.50mm -1 Up to 1.00mm -1 , 1.00mm -1Up to 3.00mm -1 , 1.00mm -1 Up to 2.50mm -1 , 1.00mm -1 Up to 2.00mm -1 , 1.00mm -1 Up to 1.50mm -1 , 1.50mm -1 Up to 3.00mm -1 , 1.50mm -1 Up to 2.50mm -1 , 1.50mm -1 Up to 2.00mm -1 , 2.00mm -1 Up to 3.00mm -1 , or 2.00mm -1 Up to 2.50mm -1 within the range.
[0025] In an embodiment, the bicomponent fiber comprises a first region and a second region, wherein the weight ratio of the first region to the second region is from 90:10 to 10:90. All individual values and subranges of the ratio from 90:10 to 10:90 are disclosed and included herein. For example, in an embodiment, the weight ratio of the first region to the second region can be from 80:20 to 20:80, from 70:30 to 30:70, from 60:40 to 40:60, or from 55:45 to 45:55.
[0026] Although the fibers taught herein are bicomponent fibers, it will be understood by those of ordinary skill in the art that because both regions of the fiber contain polyethylene compositions, it may not be easy to discern from the fiber itself that the fiber includes two different regions. It will be understood by those of ordinary skill in the art that Raman microscopy and multivariate calibration as described in the test methods section below can be used to measure the percent (%) crystallinity of individual polyethylene regions of bicomponent fibers in situ. The difference between the Raman measured crystallinity% of the two regions of the bicomponent fiber according to an embodiment of the present disclosure corresponds to the improved curvature of the fiber. In an embodiment, the Raman measured crystallinity% of the first polyethylene composition of the first region of the bicomponent fiber is at least 5.0% greater than the Raman measured crystallinity% of the second polyethylene composition of the second region of the bicomponent fiber, wherein the Raman measured crystallinity% is measured according to the test method described below. All individual values and subranges of at least 5.0% greater are disclosed and included herein; for example, the Raman-measured % crystallinity of a first polyethylene composition in a first region of a bicomponent fiber can be at least 5.0% greater, at least 7.5% greater, at least 10.0% greater, or between 5.0% and 20.0% greater, between 5.0% and 15.0% greater, between 7.5% and 15.0% greater, between 10.0% and 15.0% greater, between 3.5% and 12.0% greater, between 5.0% and 12.0% greater, between 7.5% and 12.0% greater, or between 10.0% and 12.0% greater than the Raman-measured % crystallinity of a second polyethylene composition in a second region of the bicomponent fiber, wherein the Raman-measured % crystallinity is measured according to the test method described below.
[0027] Centroid
[0028] In an embodiment, a bicomponent fiber comprises a fiber centroid and a first region having a first centroid and a second region having a second centroid, wherein at least one of the first centroid and the second centroid is different than the fiber centroid.
[0029] As used herein, the term "centroid" refers to the arithmetic mean of all points of the cross-sectional area of a bicomponent fiber. For example, a bicomponent fiber according to an embodiment of the present disclosure has a fiber centroid, which can be designated as C f , and a region of the bicomponent fiber (e.g., the first region or the second region) has an independent centroid, which can be named C rx , where x is the name of the region (for example, the first region can be named C r1 And the second region can be named C r2 ), and where "r" is C f The average distance from the outer surface of the bicomponent fiber and is calculated as Where A is the area of the bicomponent fiber cross section. Figure 1The bicomponent fiber and its centroid and the centroid of a second region of the bicomponent fiber are shown. The distance from the region centroid to the fiber centroid can be defined as "P rx ”, and the centroid offset of the first centroid or the second centroid from the fiber centroid can be defined as “P rx / r”.
[0030] In an embodiment, at least one of the first centroid and the second centroid is different from the fiber centroid. In the case where the first centroid or the second centroid is different from the fiber centroid, the bicomponent fiber can have different configurations, such as eccentric core-sheath, side by side or split pie, but cannot have a concentric configuration (e.g., a core-sheath concentric configuration), in which the fiber centroid, the first centroid and the second centroid are the same. In an embodiment, the first centroid of the first region and the second centroid of the second region are arranged so that the first region and the second region are in a side-by-side configuration. In other embodiments, the first centroid of the first region and the second centroid of the second region are arranged so that the first region and the second region are in a split pie configuration. In other embodiments, the first centroid of the first region and the second centroid of the second region are arranged so that the first region and the second region are in an eccentric core-sheath configuration, wherein the first region is the sheath of the bicomponent fiber, and the second region is the core region of the bicomponent fiber, and the sheath region surrounds the core region.
[0031] In embodiments, the first or second centroid is offset from the fiber centroid by at least 0.1, or at least 0.2, or at least 0.4, and less than 1, or less than 0.9, wherein the offset is measured according to the test method described below.
[0032] First and Second Regions - Metallocene or Single Site Catalyst Embodiments
[0033] In certain embodiments, the bicomponent fiber comprises a first region and a second region; the first region comprises a first polyethylene composition having a molecular weight expressed as a ratio of weight average molecular weight to number average molecular weight (M) of less than 3.0. w(GPC) / M n(GPC) ) molecular weight distribution; the second region comprises a second polyethylene composition having a density less than the density of the first polyethylene composition; wherein the crystallization temperature (Tc) of the first polyethylene composition is at least 2°C greater than the crystallization temperature (Tc) of the second polyethylene composition. In such embodiments, the first polyethylene composition can be formed in the presence of a metallocene or single site catalyst.
[0034] Further, in such embodiments, the first polyethylene composition has a ratio (M) expressed as weight average molecular weight to number average molecular weight of less than 3.0. w(GPC) / M n(GPC)) molecular weight distribution. Disclosed herein and including molecular weight distribution (M) less than 3.0 w(GPC) / M n(GPC) ) all individual values and subranges; for example, in an embodiment, the molecular weight distribution (M w(GPC) / M n(GPC) ) is less than 3.0, less than 2.8, less than 2.6, less than 2.4, or less than 2.2, or in the range of 1.8 to 3.0, 1.8 to 2.6, 1.8 to 2.4, 1.8 to 2.2, 2.0 to 3.0, 2.0 to 2.6, 2.0 to 2.4, 2.0 to 2.2, 2.2 to 2.6, or 2.2 to 2.4, wherein the molecular weight distribution can be expressed as the ratio of the weight average molecular weight to the number average molecular weight ((M w(GPC) / M n(GPC) ) and can be measured according to the test method described below.
[0035] In addition, in such embodiments, the crystallization temperature (Tc) of the first polyethylene composition is at least 2°C greater than the crystallization temperature (Tc) of the second polyethylene composition. All individual values and subranges of the crystallization temperature (Tc) of the first polyethylene composition that are at least 2°C greater than the crystallization temperature (Tc) of the second polyethylene composition are disclosed and included herein; for example, the crystallization temperature (Tc) of the first polyethylene composition may be at least 2°C greater, at least 4°C greater, at least 6°C greater, at least 8°C greater, at least 10°C greater, at least 12°C greater, at least 14°C greater, at least 16°C greater, or at least 18°C greater than the crystallization temperature (Tc) of the second polyethylene composition, or the crystallization temperature (Tc) of the first polyethylene composition minus the crystallization temperature (Tc) of the second polyethylene composition. The difference in crystallization temperature (Tc) can be in the range of 2°C to 30°C, 2°C to 25°C, 2°C to 20°C, 2°C to 15°C, 2°C to 10°C, 2°C to 5°C, 5°C to 30°C, 5°C to 25°C, 5°C to 20°C, 5°C to 15°C, 5°C to 10°C, 10°C to 30°C, 10°C to 25°C, 10°C to 20°C, 10°C to 15°C, 15°C to 30°C, 15°C to 25°C, or 15°C to 20°C, wherein the crystallization temperature (Tc) can be measured according to differential scanning calorimetry (DSC) as described below.
[0036] In addition, in such embodiments, the melting temperature (Tm) of the first polyethylene composition can be at least 2°C greater than the melting temperature (Tm) of the second polyethylene composition. All individual values and subranges of the melting temperature (Tm) of the first polyethylene composition that are at least 2°C greater than the melting temperature (Tm) of the second polyethylene composition are disclosed and included herein; for example, the melting temperature (Tm) of the first polyethylene composition can be at least 2°C greater, at least 4°C greater, at least 6°C greater, at least 8°C greater, at least 10°C greater, at least 14°C greater, at least 18°C greater, at least 22°C greater, or at least 26°C greater, or at least 30°C greater than the melting temperature (Tm) of the second polyethylene composition, or the difference between the melting temperature (Tm) of the first polyethylene composition minus the melting temperature (Tm) of the second polyethylene composition can be between 2°C and 50°C, between 2°C and 45°C, between 2°C and 40°C, between 2°C and 35°C, between 2°C and 2°C, between 2°C and 35°C, between 2°C and 45°C, between 2°C and 3 ... ℃ to 30°C, 2°C to 25°C, 2°C to 20°C, 2°C to 15°C, 2°C to 10°C, 2°C to 5°C, 5°C to 50°C, 5°C to 45°C, 5°C to 40°C, 5°C to 35°C, 5°C to 30°C, 5°C to 25°C, 5°C to 20°C, 5°C to 15°C, 5°C to 10°C, 10°C to 50°C, 10°C to 40°C, 10°C to 30°C, 10°C to 20°C, 20°C to 50°C, 20°C to 40°C, 20°C to 30°C, 25°C to 50°C, 25°C to 40°C, 25°C to 35°C, 30°C to 50°C, 30°C to 40°C, 30°C to 35°C, or 30°C to 32°C, wherein the melting temperature can be measured according to DSC as described below.
[0037] In addition, in such embodiments, the melting temperature (Tm) of the first polyethylene composition can be less than 130° C. All individual values and subranges less than 130° C. are disclosed and included herein; for example, the melting temperature (Tm) of the first polyethylene composition can be less than 130° C., less than 129.8° C., less than 129.6° C., less than 129.4° C., less than 129.2° C., less than 129° C., or less than 128.9° C., wherein the melting temperature (Tm) can be measured according to DSC as described below. In an embodiment, the melting temperature (Tm) of the second polyethylene composition can be less than 127° C. All individual values and subranges less than 127°C are disclosed and included herein; for example, the melting temperature (Tm) of the second polyethylene composition can be less than 127°C, less than 126.5°C, less than 125°C, less than 120°C, less than 115°C, less than 110°C, less than 105°C, less than 100°C, less than 99°C, less than 98.5°C, or less than 98°C, where the melting temperature (Tm) can be measured according to DSC as described below.
[0038] In an embodiment, the difference of the melting temperature (Tm) of the first polyethylene composition minus the melting temperature (Tm) of the second polyethylene composition may be at least 1.5°C. All individual values and subranges of at least 1.5°C are included and disclosed herein; for example, the difference of the melting temperature (Tm) of the first polyethylene composition minus the melting temperature (Tm) of the second polyethylene composition may be at least 1.5°C, at least 2.0°C, at least 2.5°C, at least 3°C, at least 5°C, at least 10°C, at least 15°C, at least 20°C, at least 25°C, or at least 30°C, or may be between 1.5°C and 40°C, 2.0°C and 40°C, 2.5°C and 40°C, 1.5°C and 30°C, 2.0°C and 30°C, 2.5°C and 30°C, 1.5°C and 30°C, 2.5°C and 30°C, 1.5°C and 40°C, 2.5°C and 30°C, 1.5°C and 3 ... ℃ to 20 ℃, 2.0 ℃ to 20 ℃, 2.5 ℃ to 20 ℃, 1.5 ℃ to 10 ℃, 2.0 ℃ to 10 ℃, 2.5 ℃ to 10 ℃, 1.5 ℃ to 5 ℃, 2.0 ℃ to 5 ℃, 2.5 ℃ to 5 ℃, 10 ℃ to 40 ℃, 10 ℃ to 35 ℃, 10 ℃ to 30 ℃, 10 ℃ to 20 ℃, 20 ℃ to 40 ℃, 20 ℃ to 35 ℃, 20 ℃ to 30 ℃, 25 ℃ to 40 ℃, 25 ℃ to 35 ℃, 28 ℃ to 32 ℃, or 29 ℃ to 31 ℃, wherein the melting temperature (Tm) can be measured according to DSC as described below.
[0039] Zone 1 and Zone 2 – Ziegler Natta Catalyst Implementation Plan
[0040] In other embodiments, the bicomponent fiber comprises a first region and a second region; the first region comprises a first polyethylene composition having a molecular weight expressed as a ratio of weight average molecular weight to number average molecular weight (M) greater than 3.0. w(GPC) / M n(GPC) ) molecular weight distribution; the second region comprises a second polyethylene composition having a density less than the density of the first polyethylene composition; wherein the crystallization temperature (Tc) of the first polyethylene composition is at least 3.5°C greater than the crystallization temperature (Tc) of the second polyethylene composition. In such embodiments, the first polyethylene composition can be formed in the presence of a Ziegler-Natta catalyst. In such embodiments, the first polyethylene composition has a molecular weight distribution expressed as a ratio of weight average molecular weight to number average molecular weight (M) greater than 3.0. w(GPC) / M n(GPC) ) molecular weight distribution. Disclosed herein and including molecular weight distribution (M) greater than 3.0 w(GPC) / M n(GPC) ) all individual values and subranges; for example, in an embodiment, the molecular weight distribution (M w(GPC) / M n(GPC)) is greater than 3.0, greater than 3.02, greater than 3.04, greater than 3.06, greater than 3.08, greater than 3.10, greater than 3.12, or greater than 3.14, or in the range of 3.0 to 5.0, 3.0 to 4.5, 3.0 to 4.0, 3.0 to 3.5, 3.0 to 3.2, 3.1 to 5.0, 3.1 to 4.5, 3.1 to 4.0, 3.1 to 3.5, or 3.1 to 3.2, wherein the molecular weight distribution can be expressed as the ratio of the weight average molecular weight to the number average molecular weight (M w(GPC) / M n(GPC) ). In such embodiments, the first polyethylene composition may be formed in the presence of a Ziegler Natta catalyst.
[0041] Furthermore, in such embodiments, the crystallization temperature (Tc) of the first polyethylene composition is at least 3.5°C greater than the crystallization temperature (Tc) of the second polyethylene composition. All individual values and subranges of the crystallization temperature (Tc) of a first polyethylene composition that is at least 3.5°C greater than the crystallization temperature (Tc) of a second polyethylene composition are disclosed herein and include; for example, the crystallization temperature (Tc) of the first polyethylene composition may be at least 3.5°C greater, at least 4°C greater, at least 4.5°C greater, at least 5°C greater, at least 5.5°C greater, at least 6°C greater, at least 6.2°C greater, or at least 6.4°C greater than the crystallization temperature (Tc) of the second polyethylene composition, or the difference between the crystallization temperature (Tc) of the first polyethylene composition minus the crystallization temperature (Tc) of the second polyethylene composition may be in the range of 3.5°C to 15°C, 3.5°C to 10°C, 3.5°C to 7.5°C, 3.5°C to 6°C, 5°C to 15°C, 5°C to 10°C, 5°C to 7.5°C, 5°C to 6°C, 6°C to 15°C, 6°C to 10°C, 6°C to 8°C, or 6°C to 7°C, wherein (Tc) can be measured according to DSC as described below.
[0042] In addition, in such embodiments, the melting temperature (Tm) of the first polyethylene composition can be at least 5°C greater than the melting temperature (Tm) of the second polyethylene composition. All individual values and subranges of the melting temperature (Tm) of the first polyethylene composition that are at least 5°C greater than the melting temperature (Tm) of the second polyethylene composition are disclosed and included herein; for example, the melting temperature (Tm) of the first polyethylene composition can be at least 5°C greater, at least 5.2°C greater, at least 5.4°C greater, at least 5.6°C greater, at least 5.8°C greater, at least 6.0°C greater, at least 6.2°C greater, and at least 6.4°C greater, at least 6.6°C greater, at least 6.8°C greater, or at least 6.9°C greater than the melting temperature (Tm) of the second polyethylene composition, or The difference of the melting temperature (Tm) of the first polyethylene composition minus the melting temperature (Tm) of the second polyethylene composition can be in the range of 5°C to 10°C, 5°C to 7.5°C, 5°C to 7°C, 5°C to 6.5°C, 5°C to 6°C, 5.5°C to 10°C, 5.5°C to 7.5°C, 5.5°C to 7°C, 5.5°C to 6°C, 6°C to 10°C, 6°C to 7.5°C, 6°C to 7°C, 6.5°C to 10°C, 6.5°C to 7.5°C, or 6.5°C to 7°C, wherein the melting temperature (Tm) can be measured according to DSC as described below.
[0043] First and second zones—usually
[0044] In embodiments described herein, the density of the second polyethylene composition is less than the density of the first polyethylene composition, wherein the density can be measured according to ASTM D792. In some embodiments, the density of the first polyethylene composition is at least 0.015 g / cm greater than the density of the second polyethylene composition. 3 This article includes and discloses at least 0.015 g / cm 3 For example, in some embodiments, the density of the first polyethylene composition is at least 0.015 g / cm greater than the density of the second polyethylene composition. 3 , at least 0.030g / cm 3 or at least 0.040g / cm 3 , or the difference between the density of the first polyethylene composition and the density of the second polyethylene composition is within 0.015 g / cm 3 Up to 0.100g / cm 3 , 0.015g / cm 3 Up to 0.080g / cm 3 , 0.015g / cm 3 Up to 0.060g / cm 3 , 0.015g / cm 3 Up to 0.040g / cm 3 , 0.015g / cm 3Up to 0.020g / cm 3 , 0.020g / cm 3 Up to 0.100g / cm 3 , 0.020g / cm 3 Up to 0.080g / cm 3 , 0.020g / cm 3 Up to 0.060g / cm 3 , 0.020g / cm 3 Up to 0.040g / cm 3 , 0.020g / cm 3 Up to 0.030g / cm 3 , 0.030g / cm 3 Up to 0.100g / cm 3 , 0.030g / cm 3 Up to 0.080g / cm 3 , 0.030g / cm 3 Up to 0.060g / cm 3 , 0.030g / cm 3 Up to 0.050g / cm 3 , 0.030g / cm 3 Up to 0.040g / cm 3 , or 0.040g / cm 3 Up to 0.050g / cm 3 The density can be measured according to ASTM D792.
[0045] In the embodiments described herein, the density of the first polyethylene composition may be at least 0.925 g / cm 3 , wherein the density can be measured according to ASTM D792. The present invention discloses and includes at least 0.925 g / cm 3 For example, in some embodiments, the density of the first polyethylene composition can be at least 0.935 g / cm 3 , at least 0.940g / cm 3 , at least 0.945g / cm 3 , at least 0.950g / cm 3 , at least 0.955g / cm 3 , at least 0.960g / cm 3 , or at least 0.965g / cm 3 , wherein the density can be measured according to ASTM D792, or the density of the first polyethylene composition can be 0.925 g / cm 3 Up to 0.980g / cm 3 , 0.930g / cm3 Up to 0.980g / cm 3 , 0.940g / cm 3 Up to 0.980g / cm 3 、0.950g / cm 3 Up to 0.980g / cm 3 , 0.930g / cm 3 Up to 0.980g / cm 3 , 0.930g / cm 3 Up to 0.970g / cm 3 , 0.930g / cm 3 Up to 0.960g / cm 3 , 0.930g / cm 3 Up to 0.950g / cm 3 , 0.940g / cm 3 Up to 0.980g / cm 3 , 0.940g / cm 3 Up to 0.970g / cm 3 , 0.940g / cm 3 Up to 0.960g / cm 3 , 0.940g / cm 3 Up to 0.950g / cm 3 , 0.945g / cm 3 Up to 0.980g / cm 3 , 0.945g / cm 3 Up to 0.970g / cm 3 , 0.945g / cm 3 Up to 0.960g / cm 3 , 0.945g / cm 3 Up to 0.955g / cm 3 、0.950g / cm 3 Up to 0.980g / cm 3 、0.950g / cm 3 Up to 0.970g / cm 3 、0.950g / cm 3 Up to 0.960g / cm 3 , 0.960g / cm 3 Up to 0.980g / cm 3 , or 0.960g / cm 3 Up to 0.980g / cm 3 The density can be measured according to ASTM D792.
[0046] In the above and embodiments described herein, the first region of the bicomponent fiber comprises at least 75 wt % of the first polyethylene composition. All individual values and subranges of at least 75 wt % are included and disclosed herein; For example, the first region can comprise at least 75 wt %, at least 80 wt %, at least 85 wt %, at least 90 wt %, at least 95 wt % or at least 75 wt % to 100 wt %, 75 wt % to 90 wt %, 75 wt % to 80 wt %, 80 wt % to 100 wt % or 90 wt % to 100 wt % of the first polyethylene composition, wherein the weight percentage is based on the gross weight of the first region.
[0047] In the above and embodiments described herein, the second zone of bicomponent fiber comprises at least 75 wt % of the second polyethylene composition. All individual values and subranges of at least 75 wt % are included and disclosed herein; For example, the second zone can comprise at least 75 wt %, at least 80 wt %, at least 85 wt %, at least 90 wt %, at least 95 wt % or at least 75 wt % to 100 wt %, 75 wt % to 90 wt %, 75 wt % to 80 wt %, 80 wt % to 100 wt % or 90 wt % to 100 wt % of the second polyethylene composition, wherein weight percent is based on the gross weight of the second zone.
[0048] In the embodiments described above and herein, the first region and / or the second region may include additional components, such as one or more other polymers and / or one or more additives. Other polymers may include polyester, another polyethylene composition, a propylene-based polymer (e.g., a polypropylene homopolymer, a propylene-ethylene copolymer, or a propylene / alpha-olefin interpolymer) or a propylene-based plastomer or elastomer. Based on the total weight of the first region or the second region comprising such other polymers, the amount of the other polymer may be up to 25 wt %. For example, in an embodiment, the first region and / or the second region may include up to 25 wt % of a propylene-based plastomer or a propylene-based elastomer (e.g., VERSIFY® available from The Dow Chemical Company). TM Polymers and VISTAMAXX available from ExxonMobil Chemical Co. TM Polymers), low modulus and / or low molecular weight polypropylene (e.g. L-MODU from Idemitsu TMPolymers), random copolymers of polypropylene or propylene-based olefin block copolymers (such as Intune). Potential additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, pigments, primary antioxidants, secondary antioxidants, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, deodorants, antifungal agents, and combinations thereof. Based on the weight of the first region or the second region containing such additives, the first region and / or the second region may contain about 0.01 wt % or 0.1 wt % or 1 wt % to about 25 wt % or about 20 wt % or about 15 wt % or about 10 wt % of such additives by combined weight.
[0049] polymerization
[0050] Any conventional polymerization method can be used to produce the first polyethylene composition or the second polyethylene composition. Such conventional polymerization methods include, but are not limited to, solution polymerization methods using one or more conventional reactors (e.g., loop reactors, isothermal reactors, stirred tank reactors, batch reactors, and / or any combination thereof in parallel or in series). Such conventional polymerization methods also include gas phase, solution, or slurry polymerization or any combination thereof using any type of reactor or reactor configuration known in the art.
[0051] In an embodiment, the solution phase polymerization process occurs in one or more well-stirred reactors (such as one or more loop reactors) at a temperature in the range of 115°C to 250°C; for example, 155°C to 225°C and at a pressure in the range of 300psi to 1000psi; for example, 400psi to 750psi. In one embodiment, in a dual reactor, the temperature in the first reactor is in the range of 115°C to 190°C (for example, 115°C to 150°C), and the second reactor temperature is in the range of 150°C to 200°C (for example, 170°C to 195°C). In another embodiment, in a single reactor, the temperature in the reactor is in the range of 115°C to 250°C (for example, 155°C to 225°C). The residence time in the solution phase polymerization process is generally in the range of 2 minutes to 30 minutes; for example, 10 minutes to 20 minutes. Ethylene, solvent, one or more catalyst systems, optionally one or more cocatalysts, optionally one or more impurity scavengers, and optionally one or more comonomers are continuously fed to one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents can be purchased from ExxonMobil Chemical Company in Houston, Texas, under the name ISOPAR E. The resulting mixture of the first polyethylene composition or the second polyethylene composition and the solvent is then taken out from the reactor, and the first polyethylene composition or the second polyethylene composition is separated. The solvent is typically recovered via a solvent recovery unit (i.e., a heat exchanger and a vapor liquid separator drum), and is subsequently recycled back into the polymerization system.
[0052] In one embodiment, the first polyethylene composition or the second polyethylene composition can be produced via a solution polymerization process in a dual reactor system (e.g., a dual loop reactor system), wherein ethylene and optionally one or more alpha-olefins are polymerized in the presence of one or more catalyst systems. In another embodiment, the first polyethylene composition or the second polyethylene composition can be produced via a solution polymerization process in a single reactor system (e.g., a loop reactor system), wherein ethylene and optionally one or more alpha-olefins are polymerized in the presence of one or more catalyst systems. As described above, in certain embodiments, the first polyethylene composition is formed in the presence of a metallocene or single-site catalyst system. In other embodiments, the first polyethylene composition is formed in the presence of a Ziegler-Natta catalyst system.
[0053] An example of a catalyst system suitable for producing the second polyethylene composition may be a catalyst system comprising a precatalyst component comprising a metal-ligand complex of formula (I):
[0054]
[0055] In formula (I), M is a metal selected from titanium, zirconium or hafnium, the metal having a formal oxidation state of +2, +3 or 4; n is 0, 1, or 2; when n is 1, X is a monodentate ligand or a bidentate ligand; when n is 2, each X is a monodentate ligand and is the same or different; the metal-ligand complex is electrically neutral as a whole; each Z is independently selected from -O-, -S-, -N(R N )-, or –P(R P )-, where independently each R N and R P is (C1-C30)alkyl or (C1-C30)heteroalkyl; L is (C1-C 40 )alkylene or (C1-C 40 )heteroalkylene, wherein (C1-C 40 ) the alkylene group has a moiety (to which L is bonded) comprising a 1-carbon atom to a 10-carbon atom connecting the main chain of the two Z groups in formula (I), or (C1-C 40 ) heteroalkylene has a moiety comprising a 1-atom to 10-atom connecting backbone connecting two Z groups in formula (I), wherein (C1-C 40 ) heteroalkylene group, wherein each of the 1-atom to 10-atom connected main chain atoms is independently a carbon atom or a heteroatom, wherein each heteroatom is independently O, S, S(O), S(O)2, Si(R C )2、Ge(R C )2. P(R C ) or N(R C ), where each R C Independently (C1-C 30 ) alkyl or (C1-C 30 ) heteroalkyl; R 1 and R 8 Independently selected from the group consisting of: -H, (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2.-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=NR C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(RN )2NC(O)-, halogen and a group having formula (II), formula (III) or formula (IV):
[0056]
[0057] In formula (II), (III) and (IV), R 31-35 , R 41-48 or R 51-59 Each of which is independently selected from (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2, -N=CHR C 、-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R N )2NC(O)-, halogen or -H, provided that R 1 or R 8 At least one of them is a group having formula (II), formula (III) or formula (IV), wherein R C , R N and R P As defined above.
[0058] In formula (I), R 2-4 , R 5-7 and R 9-16 Each of which is independently selected from (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2, -N=CHR C 、-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(RC )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R C )2NC(O)-, halogen and -H, where R C , R N and R P As defined above.
[0059] Catalyst systems comprising the metal-ligand complex of formula (I) may be rendered catalytically active by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, the metal-ligand complex of formula (I) may be rendered catalytically active by contacting the complex with an activating cocatalyst or combining the complex with an activating cocatalyst. Activating cocatalysts suitable for use herein include alkylaluminums; polymeric or oligomeric aluminoxanes (also referred to as aluminoxanes); neutral Lewis acids; and non-polymeric, non-coordinating, ion-forming compounds (including the use of such compounds under oxidizing conditions). A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" means a monoalkylaluminum dihydride or monoalkylaluminum dihalide, a dialkylaluminum hydride or dialkylaluminum halide, or a trialkylaluminum. Examples of polymeric or oligomeric aluminoxanes include methylaluminoxane, methylaluminoxane modified with triisobutylaluminum, and isobutylaluminoxane.
[0060] Lewis acid activators (cocatalysts) include those containing 1 to 3 (C1-C 20 ) hydrocarbyl substituent. Examples of Group 13 metal compounds are tri((C1-C 20 ) alkyl) substituted aluminum or tri((C1-C 20 ) alkyl)-boron compounds; tri(alkyl)-substituted aluminum, tri((C1-C 20 )alkyl)-boron compounds; tri((C1-C 10 )alkyl)aluminum, tri((C6-C 18 ) aryl) boron compounds; and their halogenated (including perhalogenated) derivatives. In another example, the Group 13 metal compound is tri(fluoro-substituted phenyl) borane, tri(pentafluorophenyl) borane. The activating cocatalyst may be tri((C1-C 20 ) alkyl borate (e.g. trityl tetrafluoroborate) or tris((C1-C 20 )alkyl)tetra((C1-C 20 As used herein, the term "ammonium" refers to a nitrogen cation that is ((C1-C20 )alkyl)4N + 、((C1-C 20 )alkyl)3N(H) + 、((C1-C 20 )alkyl)2N(H)2 + 、(C1-C 20 )Hydrocarbon N(H)3 + or N(H)4 + , where there are two or more (C1-C 20 ) hydrocarbon groups, they may be the same or different.
[0061] The combination of a neutral Lewis acid activator (cocatalyst) comprises a tri((C1-C4)alkyl)aluminum and a tri((C6-C 18 The present invention can be used in combination with a neutral Lewis acid mixture of a (metal-ligand complex): (tris(pentafluorophenylborane): (aluminoxane) [e.g., (Group 4 metal-ligand complex): (tris(pentafluorophenylborane): (aluminoxane)] in a ratio of moles of 1:1:1 to 1:10:30, or 1:1:1.5 to 1:5:10.
[0062] The metal-ligand complex catalyst system comprising formula (I) can be activated by combining with one or more cocatalysts (e.g., cation-forming cocatalysts, strong Lewis acids, or combinations thereof) to form an active catalyst composition. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes (especially methylaluminoxane) and inert, compatible, non-coordinating, ion-forming compounds. Exemplary suitable cocatalysts include, but are not limited to, modified methylaluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyltetrakis(pentafluorophenyl)boric acid (1 - )amines, and combinations thereof.
[0063] One or more of the aforementioned activating cocatalysts may be used in combination with one another. A preferred combination is a mixture of tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane or ammonium borate with an oligomeric or polymeric aluminoxane compound. The ratio of the total number of moles of the one or more metal-ligand complexes of formula (I) to the total number of moles of the one or more activating cocatalysts in the activating cocatalyst is 1:10,000 to 100:1. The ratio may be at least 1:5000, or at least 1:1000; and may not exceed 10:1 or not exceed 1:1. When aluminoxane is used alone as an activating cocatalyst, the number of moles of aluminoxane employed is preferably at least 100 times the number of moles of the metal-ligand complex of formula (I). When tri(pentafluorophenyl)borane is used alone as an activating co-catalyst, the ratio of the number of moles of tri(pentafluorophenyl)borane employed to the total number of moles of the one or more metal-ligand complexes of formula (I) may be 0.5: 1 to 10: 1, 1: 1 to 6: 1, or 1: 1 to 5: 1. The remaining activating co-catalyst is typically employed in a molar amount approximately equal to the total molar amount of the one or more metal-ligand complexes of formula (I).
[0064] Test Method
[0065] density
[0066] Density is measured according to ASTM D792 and is expressed in grams / cm 3 (g / cm 3 )express.
[0067] Melt index (I2)
[0068] Melt index (I2) is measured according to ASTM D1238 at 190 degrees Celsius (°C) and 2.16 kg and is expressed in grams eluted per 10 minutes (g / 10 min).
[0069] Curvature
[0070] The amount of curvature was measured via an optical microscope. The amount of curvature was calculated based on the inverse of the radius of the spiral formed by the fiber. This is equal to the radius of the circle formed by the projection of the spiral formed by the fiber on a surface perpendicular to it. The average of at least 5 measurements is reported. The measurements are in 1 / mm -1 ) is reported by the unit.
[0071] Center of mass offset
[0072] The fibers were embedded in epoxy and polished under cryogenic conditions using a Leica UCT / FCS microtome operating at -140°C for AFM analysis. The topographic and phase images were captured at ambient temperature using a Bruker Icon AFM system with a MikroMasch probe. The probe had a spring constant of 40 N / m and a resonant frequency of about 170 kHz. An imaging frequency of 0.5 Hz-2 Hz and a set point ratio of about 0.8 were used. The diameter of the fiber cross section was measured using a single cord, and this measurement was divided into two halves to mark the midpoint as the fiber center of mass (Cf). The core region of the bicomponent fiber was divided by two cords at 90° to visually produce four quadrants of equal area, and the intersection of the two cords defined the center of mass (Cr2) of the core region. The distance between the fiber center of mass (Cf) and the center of mass (Cr2) of the core region was measured and then divided by the radius of the fiber to calculate the fiber center of mass offset (Pr2 / r).
[0073] Conventional GPC (Mw / Mn)
[0074] Conventional GPC was obtained by high temperature gel permeation chromatography (GPC) equipment (PolymerChar, Spain). An IR5 detector ("measurement channel") was used as a concentration detector. GPCOne software (PolymerChar, Spain) was used to calculate the weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer and to determine the molecular weight distribution (Mw / Mn). The method used three 10 micron PL gel mixed B columns (Agilent Technologies, column dimensions 100 mm×7.6 mm) or four 20 micron PL gel mixed A columns (Agilent Technologies, column dimensions 100 mm×7.6 mm) operated at a system temperature of 150°C. Samples with a concentration of 2 mg / mL were prepared by an autosampler (PolymerChar, Spain) in a 1,2,4-trichlorobenzene solvent containing 200 percent of the antioxidant butylated hydroxytoluene (BHT) at 160°C under gentle shaking for 3 hours. The flow rate was 1.0 mL / min and the injection size was 200 microliters. GPCOne software is used to calculate the plate count. The chromatography system must have at least 22,000 plates.
[0075] The GPC column set was calibrated by running at least 20 narrow molecular weight distribution polystyrene standards. The calibration used a third order fit for a system with three 10 micron PL Gel Mixed B columns, or a fifth order fit for a system with four 20 micron PL Gel Mixed A columns. The molecular weight (MW) range of the standards was from 580 g / mol to 8,400,000 g / mol, and the standards were contained in 6 "cocktail" mixtures. Each standard mixture had approximately ten degrees of resolution between the individual molecular weights. These standard mixtures were purchased from Agilent Technologies. The polystyrene standards were prepared as follows: for molecular weights equal to or greater than 1,000,000 g / mol, they were prepared as "0.025 g in 50 mL of solvent", and for molecular weights less than 1,000,000 g / mol, they were prepared as "0.05 g in 50 mL of solvent". The polystyrene standards were dissolved at 80°C for 30 minutes with gentle stirring. The narrow standards mixtures were run first and in order of decreasing highest molecular weight component to minimize degradation. The polystyrene standard peak molecular weights were converted to polyethylene molecular weights using equation (1) (as described by Williams and Ward, J. Polym. Sci., Polym. Letters, 6, 621 (1968)):
[0076] MW PE =A×(MW PS )B(Equation 1)
[0077] Wherein MW is the molecular weight of the polyethylene (PE) or polystyrene (PS) being labeled, and B is equal to 1.0. It is known to those of ordinary skill in the art that A can be in the range of about 0.38 to about 0.44, so that the A value produces 52,000 MWPE for the standard reference material (SRM) 1475a. This polyethylene calibration method is used herein to obtain molecular weight values (e.g., molecular weight distribution (MWD or Mw / Mn)) and related statistical data as defined as the modified Williams and Ward method. Number average molecular weight, weight average molecular weight, and z average molecular weight are calculated by the following equations.
[0078] M n,cc =∑w i / ∑(w i / M cc,i ) (Equation 2)
[0079] M w,cc =∑w i M cc,i (Equation 3)
[0080]
[0081] Among them, Mn,cc 、M w,cc and M z,cc (in g / mol) are the number average molecular weight, weight average molecular weight and z average molecular weight obtained from conventional calibration, respectively. i The reserved volume V i The weight fraction of polyethylene molecules eluted at cc,i is obtained using conventional calibration at the retention volume V i The molecular weight (in g / mol) of the polyethylene molecule eluted at 40 °C (see Eq. (1)).
[0082] When viewing the chromatogram at 20% peak height, the peak should be set to include the region where the marker deviates significantly from the baseline. The baseline integral should not be less than 100 polyethylene equivalent molecular weight, and care must be taken to handle mismatches between the antioxidant and the prepared sample and chromatographic mobile phase.
[0083] The use of a decane flow rate marker is shown in the IR5 chromatogram. The baseline (response) Y value difference between the baseline start and end should not be greater than 3% of the chromatogram integrated peak height at any time. In this case, the chromatographic sample must be processed by properly matching the sample and mobile phase antioxidants.
[0084] w(greater than 10 5 g / mol) according to equation (5) according to the MWD curve (w i log M cc,i )calculate
[0085]
[0086] Differential Scanning Calorimetry (DSC)
[0087] DSC is used to measure the melting temperature (Tm) and crystallization temperature (Tc) characteristics of polymers at a wide range of temperatures. For example, a TA Instruments Q1000 DSC equipped with an RCS (refrigerated cooling system) and an autosampler is used to perform this analysis. During the test, a nitrogen purge gas flow of 50 ml / min is used. Each sample is melt-pressed into a film at about 175°C; the molten sample is then air-cooled to room temperature (about 25°C). Film samples are formed by extruding a "0.1 gram to 0.2 gram" sample at 175°C, 1,500 psi for 30 seconds to form a "0.1 mil to 0.2 mil thick" film. A 3mg-10mg, 6mm diameter sample is extracted from the cooled polymer, weighed, placed in a light aluminum pan (about 50 mg), and sealed with a gland. Analysis is then performed to determine its thermal properties.
[0088] The thermal behavior of the sample is determined by ramping up and down the sample temperature to produce a heat flow versus temperature curve. First, the sample is quickly heated to 180°C and isothermally held for five minutes to remove its thermal history. Next, the sample is cooled to -40°C at a cooling rate of 10°C / minute and isothermally held at -40°C for five minutes. The sample is then heated to 150°C at a heating rate of 10°C / minute (this is the "second heating" ramp). The cooling curve and the second heating curve are recorded. The cooling curve is analyzed by setting a baseline endpoint from the start of crystallization to -20°C. The heating curve is analyzed by setting a baseline endpoint from -20°C to the end of melting. The measured value is the highest peak melting temperature (T m ) (referred to herein as the melting temperature (Tm)), the highest peak crystallization temperature (Tc) (referred to herein as the "crystallization temperature (Tc)"), the heat of fusion (H f ) (in Joules / gram) and the crystallinity % of the polyethylene sample calculated using the following formula: Crystallinity % = ((H f ) / (292 J / g)) × 100. Report the heat of fusion (H) from the second heating curve f The crystallization temperature (Tc) was determined from the cooling curve.
[0089] Raman microscopy
[0090] Raman microscopy and multivariate calibration were used to measure in situ the % crystallinity of individual polyethylene regions of bicomponent fibers. Raman microscopy, as a type of vibrational spectroscopic technique, is sensitive to the vibrations of the polymer backbone and can provide information about both the amorphous and crystalline phases of polymer and polyethylene compositions. Raman can use visible or near infrared radiation and provides a lateral spatial resolution of about 0.8 microns to 1.2 microns when coupled to an optical microscope (depending on the excitation laser and microscope objective used).
[0091] A partial least squares (PLS) model was constructed to correlate the Raman data with the annealed base resin density and the percent crystallinity (%) calculated from the annealed polyethylene composition density. The annealed density was measured according to ASTM D792. The percent crystallinity (%) was calculated from the measured annealed density using the following equation (Equation 6):
[0092]
[0093] Where: a =0.855 g / cc (100% amorphous) and ρ c = 1.000 g / cc (100% crystalline) density.
[0094] Polarized Raman spectra were collected using an equivalent Thermo Scientific DXR2 micro-Raman instrument. Raman spectra were collected using a 900 grooves / mm grating. The spectral range covered 50 cm -1 Up to 3500cm -1 The Raman shift is 0.964 cm. -1 Other data acquisition parameters are as follows. Acquisition time: 3 sec-10 sec; Number of acquisitions: 3 to 6; Dark current subtraction, cosmic ray filter, and white light correction: On. Calibration data were recorded with an Olympus M PlanN 20x (0.40NA) objective using a 25 μm slit and an Olympus M PlanN 100x (0.90NA) objective using a 50 μm pinhole.
[0095] The density range of the twenty-eight samples is 0.859 g / cm 3 -0.964g / cm 3 The polyethylene composition resins of 100 μm and 100 μm were used for calibration and cross validation of the PLS model. The PLS model was also validated using an independent set of density patches and then used to measure the resin crystallinity of the resins in the region used for the bicomponent fibers. The PLS model was constructed using TQ Analyst TM Software, built with the following parameters: Spectral region: 1571 cm -1 Up to 971cm -1 ; Normalized: integrated area 1356cm -1 -1227cm -1 -Same baseline points; Total number of samples: 28; Number of calibration standards: 26; Number of independent cross-validation samples: 2; Number of independent validation samples: 6; Data pre-processing for: Annealed base resin density model and calculated crystallinity % model - average centering, 2nd derivative, SG smoothing (15 points, 3rd order polynomial); Number of factors used for calibration of both models: Annealed base resin density and calculated crystallinity % = 4.
[0096] After validating the PLS model, a longitudinal (parallel to the stretching direction) cross section of each bicomponent fiber example was prepared. The cross section was oriented on the sample stage so that the stretching direction of the fiber was oriented in the east-west direction on the sample stage. Depolarized Raman spectra were collected in three different locations in each region of the bicomponent fiber example using a 100x (0.9NA) objective and a 25 micron pinhole. The resulting Raman spectra from each region were averaged, and the averaged spectra were used to measure the regional crystallinity % using the PLS model.
[0097] Example
[0098] Synthesis of polyethylene compositions
[0099] Development resins ("Resin 1", "Resin 2", "Resin 3" and "Resin 4") were prepared according to the following methods and table.
[0100] All raw materials (monomers and comonomers) and process solvents (narrow boiling range high purity isoparaffin solvent, Isopar-E) were purified with molecular sieves before introduction into the reaction environment. Hydrogen was supplied under pressure in high purity grades without further purification. The reactor monomer feed stream was pressurized to greater than the reaction pressure via a mechanical compressor. The solvent and comonomer (if present) feeds were pressurized to greater than the reaction pressure via a pump. Individual catalyst components were manually diluted in batches with purified solvents and pressurized to greater than the reaction pressure. All reaction feed streams were measured with mass flow meters and independently controlled with computer automated valve control systems.
[0101] The reactor configuration was either single reactor operation or dual series reactor operation as specified in Table 2.
[0102] A single reactor system or two reactor systems in a series configuration are used. Each reactor is a continuous solution polymerization reactor consisting of a non-adiabatic isothermal circulation loop reactor full of liquid simulating a continuous stirred tank reactor (CSTR) with heat removal. All fresh solvents, monomers, comonomers (if present), hydrogen and catalyst component feeds can be controlled independently. The temperature of the total fresh feed stream (solvent, monomer, comonomer [if present] and hydrogen) entering each reactor is controlled by passing the feed stream through a heat exchanger, usually between 15°C-50°C to maintain a single solution phase. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, wherein there is a roughly equal reactor volume between each injection location. The fresh feed is controlled by receiving half of the total fresh feed mass flow rate with each injector. The catalyst components are injected into the polymerization reactor through an injection nozzle to introduce these components into the center of the reactor flow. The computer controls the main catalyst component feed to maintain the reactor monomer conversion at a specified value. The co-catalyst component is fed based on the calculated specified molar ratio with the main catalyst component. Immediately following each reactor feed injection location, the feed stream is mixed with the circulating polymerization reactor contents using static mixing elements. The contents of each reactor are continuously circulated through a heat exchanger which is responsible for removing most of the heat of reaction and where the temperature on the coolant side is responsible for maintaining an isothermal reaction environment at a specified temperature. Circulation around each reactor loop is provided by a pump.
[0103] In a dual series reactor configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer [if present], hydrogen, catalyst components and polymer) exits the first reactor loop and is added to the second reactor loop.
[0104] In all reactor configurations, the final reactor effluent (either the second reactor effluent in a dual series or the single reactor effluent) enters a zone where a suitable reagent (water) is added and reacts with the suitable reagent to deactivate the final reactor effluent. At this same reactor outlet location, other additives are added for polymer stabilization.
[0105] After catalyst deactivation and addition of additives, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The separated polymer melt is pelletized and collected. The non-polymer stream passes through various devices that separate most of the ethylene removed from the system. Most of the solvent and unreacted comonomer (if any) are recycled back to the reactor after passing through a purification system. Small amounts of solvent and comonomer (if any) are purged from the process.
[0106] Figure 2 and Figure 3 The reactor stream feed data flows are graphically depicted in , which correspond to the values in Table 2 used to produce the development resins. The data are presented so that the complexity of the solvent recycle system is taken into account, and the reaction system can be more simply handled as a once through flow diagram.
[0107] Table 1 - Catalyst components
[0108]
[0109] Table 2 - Production conditions
[0110]
[0111]
[0112] The following materials were used in the examples.
[0113] Polymer 1 (Poly. 1) is Resin 1 described above.
[0114] Polymer 2 (Poly.2) is ASPUN TM 6835, a polyethylene composition and linear low density polyethylene fiber resin commercially available from The Dow Chemical Company (Midland, MI).
[0115] Polymer 3 (Poly. 3) is resin 2 described above.
[0116] Polymer 4 (Poly. 4) is the resin 3 described above.
[0117] Polymer 5 (Poly. 5) is resin 4 described above.
[0118] Poly.6 is ELITE TM 5860, a polyethylene composition and a reinforced polyethylene resin commercially available from The Dow Chemical Company, Midland, Michigan.
[0119] The density, melt index (I2), molecular weight distribution (Mw / Mn), crystallization temperature (Tc), and melting temperature (Tm) of Polymers 1 to 6 are reported in Table 3 below.
[0120] Table 3 – Properties of polymers 1 to 6
[0121] polymer <![CDATA[Density (g / cm 3 )]]> Melt index (I2) Mw / Mn Tc(℃) Tm(℃) Polymer 1 0.950 19.0 2.170 114.50 128.81 Polymer 2 0.950 17.0 3.750 115.00 127.35 Polymer 3 0.968 35.0 3.144 118.23 133.18 Polymer 4 0.935 17.0 2.300 113.20 127.45 Polymer 5 0.935 21.0 2.300 111.80 126.21 Polymer 6 0.907 25.0 2.800 96.32 97.86
[0122] Fiber formation
[0123] The fiber was spun on a Hills bicomponent continuous filament fiber spinning line. Bicomponent fibers with an eccentric core-sheath configuration were manufactured. The fiber was spun on a Hills line according to the following conditions. The profile of the extruder was adjusted to achieve a melt temperature of 240°C. The throughput rate of each hole was 0.5 ghm (grams per hour per minute). A Hills bicomponent die was used and operated at a 40 / 60 core / sheath ratio (by weight) to form embodiments of the present invention 1, 2, 3 and 4, and comparative examples 1, 2, 3, 4, 5 and 6, wherein according to Table 4 below, the first zone is included in an example in one extruder and the second zone is included in another example in another extruder. The Hills line pressure was set to 40 psi. The die consisted of 144 holes, wherein the hole diameter was 0.6 mm and the length / diameter (L / D) was 4 / 1. The quench air temperature and flow rate were set to 15°C-18°C and 520 cfm (cubic feet per minute), respectively. After the quench zone, draw tension was applied to the 144 filaments by pneumatically entraining the filaments with an air stream in a slot unit. The air stream velocity was controlled by the slot aspirator pressure.
[0124] Table 4 - Fiber Examples
[0125]
[0126] Table 5 provides the melting temperature difference (ΔTm), crystallization temperature difference (ΔTc) and density difference (Δdensity) of the first region minus the second region of Examples 1 and 2 of the present invention and Comparative Examples 1 and 2, wherein the molecular weight distribution (Mw / Mn) of the polyethylene composition in the first region of these embodiments is less than 3.
[0127] Table 5 – ΔTm, Δdensity, ΔTc data
[0128]
[0129]
[0130] Table 6 provides the melting temperature difference (ΔTm), crystallization temperature difference (ΔTc) and density difference (Δdensity) of the first region minus the second region of Examples 3 and 4 of the present invention and Comparative Examples 3, 4 and 5, wherein the molecular weight distribution (Mw / Mn) of the polyethylene composition in the first region of these embodiments is greater than 3.
[0131] Table 6 - ΔTM, ΔDensity and ΔTc Data
[0132] Example ΔTm ΔTc ΔDensity Embodiment 3 of the present invention 6.97 6.43 0.033 Embodiment 4 of the present invention 5.73 5.03 0.033 Comparative Example 3 1.14 3.20 0.015 Comparative Example 4 -0.10 1.80 0.015 Comparative Example 5 5.83 3.23 0.018 Comparative Example 6 0 0 0
[0133] According to the Raman microscopy test method described above, the crystallinity % of certain inventive examples and comparative examples were tested. Table 7 shows the results.
[0134] Table 7 - % Crystallinity from Raman Microscopy
[0135]
[0136] Table 8 shows the amount of curvature associated with the examples. Inventive Examples 1 to 4 have significantly higher curvature than the comparative example having no curvature.
[0137] Table 8 – Curvature data
[0138]
[0139]
[0140] Table 9 provides center of mass offset and fiber radius data for certain examples.
[0141] Table 9 - Fiber radius and center of mass offset
[0142]
Claims
1. A bicomponent fiber, comprising: Fiber centroid; defining a core of the bicomponent fiber and a first region having a first centroid, and defining a sheath of the bicomponent fiber and a second region having a second centroid; The first region comprises a first polyethylene composition having a ratio of weight average molecular weight to number average molecular weight (M) denoted as core of 1.8 to 3.
0. w(GPC) / M n(GPC) ) of the core molecular weight distribution; The second region comprises a second polyethylene composition having a density less than a density of the first polyethylene composition; wherein at least one of the first centroid and the second centroid is different from the fiber centroid; and wherein the crystallization temperature of the first polyethylene composition is at least 2°C greater than the crystallization temperature of the second polyethylene composition.
2. The bicomponent fiber of claim 1, wherein the melting temperature of the first polyethylene composition is at least 2°C greater than the melting temperature of the second polyethylene composition.
3. The bicomponent fiber of claim 1 or 2, wherein the melting temperature of the first polyethylene composition is less than 130°C.
4. A bicomponent fiber, comprising: Fiber centroid; defining a core of the bicomponent fiber and a first region having a first centroid, and defining a sheath of the bicomponent fiber and a second region having a second centroid; The first region comprises a first polyethylene composition having a ratio of weight average molecular weight to number average molecular weight (M) denoted as core of 3.0 to 5.
0. w(GPC) / M n(GPC) ) of the core molecular weight distribution; The second region comprises a second polyethylene composition having a density less than a density of the first polyethylene composition; wherein at least one of the first centroid and the second centroid is different from the fiber centroid; wherein the crystallization temperature of the first polyethylene composition is at least 3.5°C greater than the crystallization temperature of the second polyethylene composition.
5. The bicomponent fiber of claim 4, wherein the melting temperature of the first polyethylene composition is at least 5°C greater than the melting temperature of the second polyethylene composition.
6. The bicomponent fiber of claim 1, 2, 4 or 5, wherein the density of the first polyethylene composition is at least 0.015 g / cm greater than the density of the second polyethylene composition. 3 .
7. The bicomponent fiber of claim 1, 2, 4 or 5, wherein the curvature of the fiber is greater than 0.5 mm. -1 .
8. The bicomponent fiber of any one of claims 1, 2, 4, or 5, wherein the Raman measured % crystallinity of the first polyethylene composition is at least 5.00% greater than the Raman measured % crystallinity of the second polyethylene composition.
9. A spunbond nonwoven comprising the bicomponent fiber according to any one of claims 1 to 8.
Citation Information
Patent Citations
Polyethylene composite fiber and a non-woven fabric using the same
US20020034635A1